2021
DOI: 10.1182/blood-2021-152027
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide CRISPR-Cas9 Screen Identifies Rationally Designed Combination Therapies Relevant for CRLF2-Rearranged Ph-like ALL

Abstract: Philadelphia chromosome-like acute lymphoblastic leukemia (Ph-like ALL, also known as BCR-ABL1-like ALL) is a disease entity of B-cell ALL that exhibits a gene expression profile, similar to that of Philadelphia chromosome-positive ALL. Ph-like ALL is categorized into two disease subtypes: "ABL-class"- and "CRLF2/JAK pathway"-types, both of which harbor gene alterations that constitutively activate cytokine/growth factor-related signals. Ph-like ALL with the CRLF2 rearrangement exhibits poor clinical outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Cells used in this study are listed in Online Supplementary Tables S1 and S2. YCUB5 (30) and KOPN49 (22,31) were provided by Hiroaki Goto (Kanagawa Children's Medical Center) and Takeshi Inukai (University of Yamanashi), respectively. Cell authentication was made using the GenePrint 10 System (Promega) with Expasy Cellosaurus short tandem repeat (STR) reference, except for YCUB5 and KOPN49, which lacked such reference.…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells used in this study are listed in Online Supplementary Tables S1 and S2. YCUB5 (30) and KOPN49 (22,31) were provided by Hiroaki Goto (Kanagawa Children's Medical Center) and Takeshi Inukai (University of Yamanashi), respectively. Cell authentication was made using the GenePrint 10 System (Promega) with Expasy Cellosaurus short tandem repeat (STR) reference, except for YCUB5 and KOPN49, which lacked such reference.…”
Section: Cellsmentioning
confidence: 99%
“…Others include combinatorial inhibition targeting JAK2 together with Bcl2 and BclxL (18) or phosphatidylinositol 3-kinase (PI3K)/mammalian target of rapamycin (19,20). Additionally, recent studies reported that GSPT1 (21), CRKL, MEK1/2 (22), HMGN1 (23), and B cell receptor-like signaling (24) are important targets for better treatment. Combinations of ruxolitinib with chemotherapeutic drugs provide additional options (25).…”
Section: Introductionmentioning
confidence: 99%